Paciente masculino de 5 años de edad con asma bronquial. - Calvache Rivera, Melanie Adriana (2021)
Asthma is a syndrome that causes inflammation and narrowing of the airways. This causes wheezing, shortness of breath, chest tightness, and cough. Due to industrial development, there has been an increase in the child population. In this bibliographic review, an attempt will be made to compile the tests used for diagnosis, their classification and the most frequently used treatments. This research study, whose objective is to identify the age range that is most affected by childhood asthma, determine the incidence of constants such as socioeconomic level, sex, race to suffer childhood asthma, prevent complications that develop in patients with asthma infant, promote habits of prevention of predisposing factors. In the different chapters the objective, the problem, and the justification of the study will be disclosed, as well as the theoretical framework, we present the definition, main risk factors and complications of asthma both locally and globally and show the reader the most important aspects.